2014
DOI: 10.1128/jcm.00420-14
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Enterohemorrhagic Escherichia coli O111 and O157 Strains Isolated from Outbreak Patients in Japan

Abstract: In April and May 2011, there was a serious food-poisoning outbreak in Japan caused by enterohemorrhagic Escherichia coli (EHEC) strains O111:H8 and O157:H7 from raw beef dishes at branches of a barbecue restaurant. This outbreak involved 181 infected patients, including 34 hemolytic-uremic syndrome (HUS) cases (19%). Among the 34 HUS patients, 21 developed acute encephalopathy (AE) and 5 died. Patient stool specimens yielded E. coli O111 and O157 strains. We also detected both EHEC O111 stx 2 and stx-negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 35 publications
2
34
1
1
Order By: Relevance
“…The single HUS patient with stx1 yielded two O111:[H8] isolates, one with stx1a + stx2a and the other with stx1a only, indicating that stx2a was the stx gene responsible for HUS development. Recently, it was demonstrated that STEC O111:H8 strains frequently lose their stx2 encoding bacteriophage during in vitro growth, suggesting that this loss may occur in vivo as well [ 3 , 51 ]. Moreover, stx1 showed a low PPV for HUS, a finding which further emphasises that stx1 was not a key factor for HUS development.…”
Section: Discussionmentioning
confidence: 99%
“…The single HUS patient with stx1 yielded two O111:[H8] isolates, one with stx1a + stx2a and the other with stx1a only, indicating that stx2a was the stx gene responsible for HUS development. Recently, it was demonstrated that STEC O111:H8 strains frequently lose their stx2 encoding bacteriophage during in vitro growth, suggesting that this loss may occur in vivo as well [ 3 , 51 ]. Moreover, stx1 showed a low PPV for HUS, a finding which further emphasises that stx1 was not a key factor for HUS development.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, O111 caused food poisoning by raw beef at branches of a barbecue restaurant in Japan. Strains without stx have also been isolated from some patients; this may be because unstable stx probacteriophases can easily drop out from O111 17) . Furthermore, food poisoning caused by sprouted vegetables occurred in Germany in 2011; patients developed HUS at a higher rate than in recent STEC infections, and fatalities were also higher.…”
Section: Discussionmentioning
confidence: 99%
“…In marked contrast, infections with enterohaemorrhagic Escherichia coli (EHEC) originate from cows, and EHEC cases have been associated with consumption of raw beef. Following an EHEC O111/O157 outbreak with fatalities that occurred in 2011 after consumption of raw bovine liver (Watahiki et al, 2014), the serving of raw bovine liver in restaurants was banned in 2012 (MHLW, 2012a). After the ban, however, it was found that restaurants serving raw meat had reportedly tended to switch to serving raw porcine liver (MHLW, 2012b); such emerging concerns are being actively discussed by the MHLW and partners.…”
Section: Discussionmentioning
confidence: 99%